Monitoring of the concrete curing process using plastic optical fibers - André, P.S.
In this paper we propose the application of plastic optical fiber to monitor the concrete curing process. The proposed method is based in the scattering of the propagated optical signal in grooves imposed to the fiber. By monitoring the intensity of the transmitted light signal, along time, we can determine the cement setting rate along all the curing period. The obtained results show that the system has enough sensitivity to analyze a curing period of 28 days, where the received optical power is 5% of the initial value.